Analisis Regresi Logistik Biner pada Pengaruh Harga, Kualitas Pelayanan dan Promosi terhadap Kepuasan Pelanggan dalam Menggunakan Jasa Layanan Grab di Kabupaten Lamongan - Ardiana Fatma Dewi; Rahmadian Pratiwi (Inferensi, 2021)
With the Covid-19 pandemic that has hit Indonesia since March 2020, people tend to choose to stay at home and take advantage of online services, one of which is a startup company called Grab. This product is welcomed by customers in various circles, price, service quality and promotion, including in the marketing strategy, have a very important role in influencing customer satisfaction. Customer loyalty will have a big impact on the company. Therefore it is necessary to carry out an analysis for online transportation service companies to find out the services provided in an effort to increase consumer loyalty. According to the 2020 BPS publication, Lamongan Regency is one of the districts in East Java which has a population of more than 1.5 million people. The large number of residents in an area opens more profit opportunities for companies, especially online services. So a research on binary logistic regression analysis was conducted to determine the satisfaction of Grab customers in Lamongan Regency with the predictor variables used, namely Price, Service Quality and Promotion. Based on the analysis, the variables that have a significant effect on customer satisfaction are Price and Customer Quality. Where the cheap price provided by Grab will affect customer satisfaction 1.475 times greater than the expensive price, and good service quality will affect customer satisfaction 1.450 times greater than poor service, with classification accuracy of 92%.